Novel strategy for reusing agricultural mulch film residual by iron modification for arsenic removal in gold-smelting wastewater - Zhang, Xiaozhuan; Zhao, Kejiang; Shi, Xibao; Tian, Zhenbang; Huang, Zuohua; Zhao, Liang (Frontiers in Chemistry, 2022)
In a gold smelting wastewater after the original treatment process of flocculation and precipitation using mainly lime, a mixture of As, Cu, Pb, Mn, Zn, Al, Ni and Fe existed with arsenic concentration of 813.07mg/L and other ions’ concentration at ug/L levels. In this work, a new clean process of mainly adsorption with self-made adsorbent Fe-PE which was synthesized by loading ferric lignin on agricultural mulch film residual, was investigated to purify and remove arsenic from the gold smelting wastewater. Batch of column experiments were investigated to explore the reaction behavior between wastewater and adsorbent Fe-PE. The results showed while operating the adsorption columns at pilot scale for 68 days, arsenic concentration in the effluent was below 0.5mg/L, and there was no significant change in the concentration of co-existing metal ions, indicating that Fe-PE had good selective adsorption performance for arsenic in wastewater. Furthermore, Fe-PE didn’t dissolve and release Fe ions in wastewater, and the whole process couldn’t produce sludge. This work firstly suggested an efficient and potential application for purification and removal of arsenic from gold smelting wastewater with agricultural mulch film residual after chemical modification, which will supply a novel strategy of reusing the agricultural mulch film residual.